El contexto sociopolítico de la formación de las nuevas generaciones de antropólogos físicos - López Alonso, Sergio (Estudios de Antropología Biológica, 2010)
The text offers some reflections about the contemporary sociopolitical environment in which the formation of a new generation of physical anthropologists occurs in Mexico. In principle, the teaching of physical anthropology in Mexico is the task of State institutions, as the result of a long historical and political process. This situation allows granting to the professional certain academic and political profiles, while imparting high social sensibility. At the present time, the impact of globalization has created new historical conditions for the treatment of old problems, highlighted by amongst other things: the responses of ethnic minorities to politics of the homogenization; the worsening of the conditions of life of the peasant and of society in general; the redefinition of politics in regard to the protection, study and diffusion of cultural patrimony, to face the process of privatization, and finally; the effects of the reduction of the federal budget dedicated to education and scientific investigation.